A point-of-care neutrophil elastase activity assay identifies bronchiectasis severity, airway infection and risk of exacerbation. Issue 6 (13th June 2019) - Shoemark, Amelia; Cant, Erin; Carreto, Luis; Smith, Alexandria; Oriano, Martina; Keir, Holly R.; Perea, Lidia; Canto, Elisabet; Terranova, Leonardo; Vidal, Silvia; Moffitt, Kelly; Aliberti, Stefano; et al.
Introduction: Neutrophil elastase activity in sputum can identify patients at high risk of airway infection and exacerbations in bronchiectasis. Application of this biomarker in clinical practice is limited, because no point-of-care test is available. We tested whether a novel semi-quantitative lateral flow device (neutrophil elastase airway test stick – NEATstik®) can stratify bronchiectasis patients according to severity, airway infection and exacerbation risk. Methods: Sputum samples from 124 patients with stable bronchiectasis enrolled in the UK and Spain were tested using the NEATstik®, which scores neutrophil elastase concentration from 0 (<8 µg·mL −1 elastase activity) to 10 (maximum detectable neutrophil elastase activity). High neutrophil elastase activity was regarded as a NEATstik® grade >6. Severity of disease, airway infection from sputum culture and exacerbations over the 12 months were recorded. An independent validation was conducted in 50 patients from Milan, Italy. Measurements and main results: Patients had a median age of 69 years and forced expiratory volume in 1 s (FEV1 ) 69%. High neutrophil elastase activity was associated with worse bronchiectasis severity using the bronchiectasis severity index (p=0.0007) and FEV1 (p=0.02). A high NEATstik® grade was associated with a significant increase in exacerbation frequency, incident rate ratio 2.75 (95% CI 1.63–4.64, p<0.001). The median time to next exacerbation for patients with a NEATstik® grade >6 was 103 days compared to 278 days. The hazard ratio was 2.59 (95% CI 1.71–3.94, p<0.001). Results were confirmed in the independent validation cohort. Conclusions: A novel lateral flow device provides assessment of neutrophil elastase activity from sputum in minutes and identifies patients at increasing risk of airway infection and future exacerbations. NEATstik®, a simple point-of-care semi-quantitative neutrophil elastase assay, can identify bronchiectasis patients with airway infection and patients at high risk of exacerbations over the subsequent 12 months http://bit.ly/2HL6OyK